Perbedaan Kemampuan Matematis Siswa pada Pembelajaran Berbasis Online dengan Model Problem-Based dan Ekspositori - Clara Natalia; Risma Uly Manalu; Santri Chintia Purba (S&Co Publishing, 2021)
This study aims to: 1) Determine the significant differences in students’ mathematical abilities using the Problem-Based Learning (PBL) and Expository learning model with Online-based learning; 2) Knowing the difference in the significant increase in students' mathematical abilities using the PBL and Expository learning model with online-based learning. The research method used is a Quasi Experiment with Nonequivalent Control Group Design. The research subjects were students of class XI MIA which consisted of 33 students in the experimental class and 35 students in the control class. The results showed that all stages of learning were in accordance with the stages of the PBL and Expository learning model. Based on statistical calculations (t-test ') with a significance level of 0.05, it was found that there was no significant difference and increase in the mathematical abilities of students who were taught the PBL and Expository learning model with Online-based learning.